1878 Gen. and Local Laws of the State of Ohio 199, div. 3, ch. 3, § 1, pt. 14 (vol. 75) - (:unkn) unknown (My University, 1878)
To regulate the transportation and keeping of gunpowder, and other explosive and dangerous combustibles, and to provide or license magazines for the same.
Keywords: GUNPOWDER - STORAGE